Thyroid hormones act as modulators of inflammation through their nuclear receptors - Lasa, Marina; Contreras-Jurado, Constanza (Frontiers in Endocrinology, 2022)
Reciprocal crosstalk between endocrine and immune systems has been well-documented both in physiological and pathological conditions, although the connection between the immune system and thyroid hormones (THs) remains largely unclear. Inflammation and infection are two important processes modulated by the immune system, which have profound effects on both central and peripheral THs metabolism. Conversely, optimal levels of THs are necessary for the maintenance of immune function and response. Although some effects of THs are mediated by their binding to cell membrane integrin receptors, triggering a non-genomic response, most of the actions of these hormones involve their binding to specific nuclear thyroid receptors (TRs), which generate a genomic response by modulating the activity of a great variety of transcription factors. In this special review on THs role in health and disease, we highlight the relevance of these hormones in the molecular mechanisms linked to inflammation upon their binding to specific nuclear receptors. In particular, we focus on THs effects on different signaling pathways involved in the inflammation associated with various infectious and/or pathological processes, emphasizing those mediated by NF-kB, p38MAPK and JAK/STAT. The findings showed in this review suggest new opportunities to improve current therapeutic strategies for the treatment of inflammation associated with several infections and/or diseases, such as cancer, sepsis or Covid-19 infection.